#Arabhealth on Instagram: Examining Public Health Messages to Arabian Gulf State Audiences. Issue 1 (2nd January 2022) - Alkazemi, Mariam F.; Guidry, Jeanine P. D.; Almutairi, Ezaddeen; Messner, Marcus
ABSTRACT: Instagram is a social media platform used for communicating health information to audiences in the member states of the Gulf Cooperation Council (GCC), but little is known about the specific use of the platform for this purpose. This study, focused on 1, 000 Instagram posts by the GCC Ministries of Health, analyzed how public health information is discussed differently across the GCC on Instagram, as well as the extent to which Health Belief Model (HBM) variables – a frequently used health behavior theory focused on understanding individual adoption of certain health behaviors – are present in these posts. Results showed that a majority of messages did not include HBM constructs other that perceived benefits and calls to action, limiting their potential for effective public health communication. Results also showed a minority of posts deal with mental health. Recommendations for future best practices are discussed.